Cervicofacial Subcutaneous Emphysema Post-Dental Procedure in A Three-Year-Old Patient: A Case Report - saputera, christina (PT Dexa Medica, 2025)
Background : Dental procedures can cause several serious complications such as cervicofacial subcutaneous emphysema, which can be fatal if not diagnosed quickly; especially in children, this is a rare case. Most of cases of cervicofacial subcutaneous emphysema present with symptoms similar to angioedema in cases of allergies, leading to misdiagnosis and delayed treatment. This case is unique because cervicofacial subcutaneous emphysema occurred before invasive dental procedures, which consisted of cleaning using a water spray. Case was taken from pediatric patient who came to the Emergency Room (ER) presented with a chief complaint swelling in the left eye area, spread to the left cheek and neck. Oxygen therapy, pain relievers, antihistamines, and antibiotics eliminate symptoms within 4 days without complications. Diagnosis carried out quickly and precisely followed by appropriate treatment results in good and complete recovery rates.